Thunder at twilight Vienna 1913/1914 - Morton, Frederic. (Boston, MA)
x, 387 sayfa, [8 ] sayfa resim
Keywords: “It was during the carnival of 1913 that a young Stalin arrived in Vienna on a mission that would launch him into the upper echelon of Russian revolutionaries, and it was here that he first collided with Trotsky. It was in Vienna that the failed artist Adolf Hitler kept daubing watercolors and spouting tirades at fellow drifters in a flophouse. Here Archduke Franz Ferdinand had a troubled audience with Emperor Franz Joseph-- and soon the bullet that killed the Archduke would set off the Great War that would kill ten million more“ --